Pandemic COVID-19: the residents’ resilience: COVID-19 and residents’ resilience - Pasin, Laura; Sella, Nicolò; Correale, Christelle; Boscolo, Annalisa; Mormando, Giulia; Zordan, Maria; Landoni, Giovanni; Navalesi, Paolo (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work. Healthcare workers are often exposed to secondary traumatic stress. The SARS-CoV-2 outbreak caused intense psychological pressure in various healthcare professionals, with increased risk of post-traumatic stress disorder. Objective of our study was to evaluate the incidence of post-traumatic stress disorder in italian residents in Intensive Care and Emergency Departments facing COVID-19 emergency. Methods. We developed a short, anonymous web-questionnaire to obtain data regarding sociodemographic, professional characteristics, history of psychological trauma, psychotherapy, use of psychiatric medications and the presence of symptoms of post-traumatic stress disorder. Primary outcome was the incidence of post-traumatic stress disorder. Secondary endpoint was to identify possible risk factors associated with the development of post-traumatic stress disorder. Post-traumatic stress disorder symptoms were assessed by the Impact of Event Scale-Revised. A cut-off of 33 identified a probable diagnosis of post-traumatic stress disorder while a cut-off of 22 identified subclinical post-traumatic stress disorder. Results. 503 residents completed the questionnaire. Among residents who were directly involved in the clinical assistance of COVID-19 patients, 34.3% presented a probable diagnosis of post-traumatic stress disorder, while 21.5% presented subclinical post-traumatic stress disorder. Female gender and history of psychological trauma were significantly associated with the development of post-traumatic stress symptoms. Conclusions. Our data suggest a high incidence of post-traumatic stress disorder in Italian residents working in Intensive Care Units and Emergency Departments during the SARS-CoV-2 outbreak. This finding supports the importance of promptly implementing any strategy that might preserve staff mental health.